Kajian Tentang Peran Emotional Branding dalam Kebangkitan UMKM F&B Lokal Pasca Gerakan BDS: - - Rafi Rahman Fauzi; Wiwi Isnaini (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2026)
The boycott of several global brands after 2023 has triggered changes in consumption patterns, particularly among Generation Z, known as digital-native consumers. This study aims to analyze how Generation Z responded to the boycott and its impact on consumption preferences for global versus local brands in the food and beverage (F&B) sector. Furthermore, this study investigates Generation Z's response to a visual campaign themed